2019
DOI: 10.3390/agronomy9080417
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CaBPM4, a BTB Domain–Containing Gene, to the Response of Pepper to Phytophthora capsici Infection and Abiotic Stresses

Abstract: The Broad-complex Tramtrack and Bric-a-brac (BTB) domain participates in plant responses to biotic and abiotic stresses, however its role is unknown in pepper plants. CaBPM4 has meprin and TRAF homology (MATH) and BTB domains at its N-and C-termini, respectively, and it contains a 1589-bp full-length cDNA that encodes a protein containing 403 amino acids. In this study, the pepper gene CaBPM4 (Capsicum annuum BTB-POZ and MATH domain protein) was cloned, and its role in responses to Phytophthora capsici, cold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Generally, BTB domain participates in plant responses against biotic and abiotic stresses. He et al, [37] reported down regulation of BTB gene under Phytophthora capsici infection. Upregulation of this gene in resistant genotype may have role in defence against F. fujikuroi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, BTB domain participates in plant responses against biotic and abiotic stresses. He et al, [37] reported down regulation of BTB gene under Phytophthora capsici infection. Upregulation of this gene in resistant genotype may have role in defence against F. fujikuroi.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, BTB domain participates in plant responses against biotic and abiotic stresses. He et al, [37] reported down regulation of BTB gene under Phytophthora capsici infection. Upregulation of this gene in resistant genotype may have role in defence against F. fujikuroi.Results of the selected DEGs showed that the qRT-PCR was consistent with the RNA-Seq results showing similar expression pattern of up-and down-regulated genes by using both, RNA-Seq and qRT-PCR, analyses.…”
mentioning
confidence: 99%
“…For example, the Ankyrin subfamily can respond to drought, salt stress, and ABA treatment, and PfBTB3/4/31/32/27/52/61 in P. fortunei belongs to the same subfamily, so we infer that these genes may be involved in similar plant stress tolerance processes. In addition, members of the MATH subfamily have been reported to be involved in plant resistance to biotic stress processes, such as CaBPM4 ( CaBTB51 ) of the MATH subfamily of pepper, which is highly regulated under the Phytophthora capsici infection [ 36 ]. These studies suggest that within the different subfamilies of BTB, each subfamily member is involved in plant-specific biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin ligases are frequently implicated under heat stress in rice ( Mittal et al, 2012 ; Zhang et al, 2012 ; González-Schain et al, 2016 ). Broad-complex Tramtrack and the Bric-a-brac (BTB) domain/POX virus and Zinc finger (POZ) (BTB/POX) domain-containing proteins (chromosome 6) are implicated in transcriptional regulation and protein degradation ( He et al, 2019 ). These BPM proteins are reported to negatively regulate the degradation of DREB2A and contribute to plant thermo-tolerance ( Morimoto et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%